2017
DOI: 10.1111/ejn.13750
|View full text |Cite
|
Sign up to set email alerts
|

Substance P and dopamine interact to modulate the distribution of delta‐opioid receptors on cholinergic interneurons in the striatum

Abstract: It has been recently demonstrated that predictive learning induces a persistent accumulation of delta-opioid receptors (DOPrs) at the somatic membrane of cholinergic interneurons (CINs) in the nucleus accumbens shell (Nac-S). This accumulation is required for predictive learning to influence subsequent choice between goal-directed actions. The current experiments investigated the local neurochemical events responsible for this translocation. We found that (1) local administration of substance P into multiple s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…D2-SPNs release enkephalin which is the endogenous ligand of DOPR (Le Merrer et al, 2009;Steiner & Gerfen, 1998) and enkephalin binding on DOPR causes these receptors to internalize, reducing membrane expression (Faget et al, 2012). Consistent with these findings, we have found that DOPR accumulation on NAc-S CINs requires concurrent D1-SPN stimulation (and SP release) and D2-SPN inhibition (Heath et al, 2018). As such, reducing D2-SPN activity should be predicted to: (1) prevent enkephalin release; (2) prevent DOPR internalization; (3) increase the accumulation of DOPR on NAc-S CINs, and (4) ensure the formation of a stable S-O memory necessary for predictive learning to guide choice between actions.…”
Section: Encoding a Cellular Memory Of Predictive Learning For Choicesupporting
confidence: 79%
See 1 more Smart Citation
“…D2-SPNs release enkephalin which is the endogenous ligand of DOPR (Le Merrer et al, 2009;Steiner & Gerfen, 1998) and enkephalin binding on DOPR causes these receptors to internalize, reducing membrane expression (Faget et al, 2012). Consistent with these findings, we have found that DOPR accumulation on NAc-S CINs requires concurrent D1-SPN stimulation (and SP release) and D2-SPN inhibition (Heath et al, 2018). As such, reducing D2-SPN activity should be predicted to: (1) prevent enkephalin release; (2) prevent DOPR internalization; (3) increase the accumulation of DOPR on NAc-S CINs, and (4) ensure the formation of a stable S-O memory necessary for predictive learning to guide choice between actions.…”
Section: Encoding a Cellular Memory Of Predictive Learning For Choicesupporting
confidence: 79%
“…To determine whether SP and NK1R are also involved in DOPR accumulation, DOPR-eGFP mice received an infusion of SP into the NAc-S in one hemisphere and SP combined with an NK1R antagonist into the contralateral hemisphere. We found that SP alone produced a robust increase in DOPR expression on CINs in the NAc-S that was abolished contralaterally in the presence of the NK1R antagonist (Heath et al, 2018). In a separate experiment, we stimulated BLA terminals in the NAc-S of DOPR-eGFP mice in the presence or absence of the NK1R antagonist (Morse et al, 2020).…”
Section: Encoding a Cellular Memory Of Predictive Learning For Choicementioning
confidence: 87%
“…We confirmed the finding that SP produces robust activation in NAc-S CINs (Figures S2I-S2K). Interestingly, we have recently reported that NAc-S infusion of SP induces DOPR accumulation in striatal CINs and that this effect is abolished by NK1R blockade (Heath et al, 2018). Accordingly, we evaluated whether NK1R antagonism could prevent BLA-mediated DOPR accumulation on NAc-S CINs.…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, the formation of outcome-specific Pavlovian predictions and their influence on choice depends on the BLA (Ostlund and Balleine, 2008) and its inputs to the NACsh (Shiflett and Balleine, 2010). In this latter case, there is now good evidence that these predictions involve BLA modulation of cholinergic processes in the shell, again mediated by CINs (Heath et al, 2018), although, importantly, both the input and output processes and the intrinsic circuitry of the NACsh differs markedly from the dorsal striatum (see Gonzales and Smith, 2015 for a thoroughgoing review of these distinctions). These stimulus-outcome relationships appear to be physically encoded in a G-protein-coupled-receptor-mediated cellular ''memory'' in the NACsh; delta opioid receptors on CINs in the shell accumulate on the membrane in a manner reflecting specific Pavlovian relationships and regulate the excitatory output from D1-expressing SPNs to medial ventral pallidum (VPm) and thence to the mdT when retrieved (Bertran-Gonzalez et al, 2013;Laurent et al, 2014;Leung and Balleine, 2015;Zahm, 1999;Figures 3B and 3d).…”
Section: Differentiating Goal-directed and Habitual Action Control In The Brainmentioning
confidence: 99%